Sumber Pendapatan Negara Dalam Konteks Ekonomi Publik Islam - Windi Prastika Sari; Fadhil, Muhammad; Endraswati, Hikam (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2025)
This study aims to analyze the sources of state revenue from the perspective of Islamic public economics and to evaluate their relevance to Indonesia's modern fiscal system. Using a literature review method, the study reveals that revenue instruments such as zakat, waqf, kharaj, and jizyah hold great potential for integration into the national public finance system to promote social justice and fiscal sustainability. However, the implementation of Islamic values remains limited due to low public literacy, inadequate regulatory frameworks, and weak institutional synergy. Therefore, institutional reform and inclusive policy strengthening are essential to optimize the role of Islamic finance as part of the national development strategy.